Conversion in Ottoman Balkans: A Historiographical Survey - Kirmizialtin, Suphan (History compass, 2007)
This article surveys the Islamization of South-eastern Europe under the Ottoman rule. In Balkan history writing the question of conversion to Islam was, and still is, a highly charged political issue. It is intrinsically linked to the issues of formation of national identities and rival territorial claims of the Balkan states. The nationalist discourse of the current Balkan historiography defines all forms of Islamization as results of the Ottoman government's centrally organized policy of forced conversion. This study argues against this position and maintains that Islamization in each Balkan country took place in the course of many centuries and its nature and phase was determined not by the Ottoman government but by the specific conditions of each locality.